Evaluasi Sistem Manajemen Keselamatan Konstruksi (SMKK) pada Proyek Pengendalian Banjir Sistem Tenggang Tahap 1 Kota Semarang - Andini Nadya Rahmawati; Anggit Tri Yatri; Eko Muliawan Satrio (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The construction sector has a high rate of workplace accidents, necessitating the implementation of an effective Construction Safety Management System (CSMS) to minimize potential hazards. This study aims to evaluate the implementation of the CSMS in the Phase I Flood Control Project of the Tenggang System in Semarang City, assess its compliance with Ministry of Public Works and Public Housing Regulation No. 10 of 2021, and analyze the level of compliance based on respondents’ perceptions. The method used was quantitative descriptive analysis through the distribution of questionnaires to 25 respondents from the Supervising Consultant team of PT Nindya–Sacna KSO. Data analysis was conducted using validity tests, reliability tests, calculation of mean values, and the Relative Importance Index (RII) using IBM SPSS Statistics. The research results indicate that all statement items are valid and reliable, with very high Cronbach’s Alpha values of 0.975, 0.909, and 0.928. The mean values fell into the high to very high categories, ranging from 4.76 to 4.96. This indicates that the implementation of SMKK has been optimal, in accordance with regulations, and has a good level of compliance, although continuous improvement is still needed to maintain consistency in its implementation.